2022
DOI: 10.1093/gigascience/giac063
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-level genome assembly ofPlazaster borealissheds light on the morphogenesis of multiarmed starfish and its regenerative capacity

Abstract: Background Plazaster borealis has a unique morphology, displaying multiple arms with a clear distinction between disk and arms, rather than displaying pentaradial symmetry, a remarkable characteristic of echinoderms. Herein we report the first chromosome-level reference genome of P. borealis and an essential tool to further investigate the basis of the divergent morphology. Findings In total, 57.76 Gb of a long read and 70.83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
(67 reference statements)
2
7
0
Order By: Relevance
“…The chromosome number is consistent with previous karyotyping studies on some asteroids, including species from Forcipulatida 53 . This is also proved by recent genome studies on several starfish species where 22 pseudo-chromosomes were identified by the Hi-C method 22 24 .…”
Section: Technical Validationmentioning
confidence: 69%
See 2 more Smart Citations
“…The chromosome number is consistent with previous karyotyping studies on some asteroids, including species from Forcipulatida 53 . This is also proved by recent genome studies on several starfish species where 22 pseudo-chromosomes were identified by the Hi-C method 22 24 .…”
Section: Technical Validationmentioning
confidence: 69%
“…cf. ophiactis genome assembly is much larger than genomes reported for other asteroids, including species in the order Forcipulatida (402–561 Mb) 21 24 , and those in the other order, Valvatida (384–608 Mb) 20 , 25 , 52 . In addition, 22 pseudo-chromosomes were generated for the Z .…”
Section: Technical Validationmentioning
confidence: 83%
See 1 more Smart Citation
“…For the sea urchin P. lividus and the black sea cucumber H. leucospilota , we used previously reported gene annotations (Chen et al 2023; Marlétaz et al 2023). We generated a draft homology-based annotation for the spiny sea star M. glacialis (Lawniczak et al 2021) with MetaEuk (Levy Karin et al 2020) using proteins of the sea urchin S. purpuratus (Spur_5.0, available in Ensembl Metazoa v56, (Sea Urchin Genome Sequencing Consortium et al 2006)), the crown-of-thorns sea star A. planci (OKI_Apl_1.0, available in Ensembl Metazoa v56 (Baughman et al 2014)) and the octopus sea star P. borealis (Lee et al 2022). One-to-one orthologous genes were identified by reciprocal best blast hit between pairs of compared genomes, using diamond (Buchfink et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The longest protein sequences of A. amurensis and other five asteroid species including Acanthaster sp . 63 , Asterias rubens 64 , Patiria miniata 65 , Plazaster borealis 66 , and Zoroaster cf. ophiactis 67 were utilized to identify orthologous groups using OrthoFinder (v2.5.5) 68 with the parameters ‘-S diamond’, and the sea urchin Lytechinus variegatus 69 was selected as an outgroup.…”
Section: Methodsmentioning
confidence: 99%